2015
DOI: 10.1111/1365-2435.12447
|View full text |Cite
|
Sign up to set email alerts
|

Beyond size – morphological predictors of bite force in a diverse insectivorous bat assemblage from Malaysia

Abstract: 1. Bite force is used to investigate feeding performance in a variety of vertebrates. In all taxa studied, bite force is strongly correlated with body and head size. Studies of bite force in bats have largely centred on neotropical species with a particular focus on species that maximize dietary differences. Little is known about the bite force of bats from the Old World tropics, nor of variation in bite force within diverse assemblages of obligate insectivores. Moreover, factors other than size are poorly kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 46 publications
2
21
0
Order By: Relevance
“…Our diceCT findings are consistent with our observations from dissections and previous gross anatomy descriptions of the bat jaw musculature (e.g., Storch , who described the cranial musculature of five species included in our sample and other bats; Herrel et al ; Senawi et al ). However, diceCT revealed finer details of muscle arrangements, attachments, and subdivisions, which highlights the utility of this method for describing and quantifying the anatomy of small muscles.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our diceCT findings are consistent with our observations from dissections and previous gross anatomy descriptions of the bat jaw musculature (e.g., Storch , who described the cranial musculature of five species included in our sample and other bats; Herrel et al ; Senawi et al ). However, diceCT revealed finer details of muscle arrangements, attachments, and subdivisions, which highlights the utility of this method for describing and quantifying the anatomy of small muscles.…”
Section: Discussionsupporting
confidence: 91%
“…Although body mass explains a large amount of the variation in bite performance across noctilionoids and other bats (Herrel et al, ; Senawi et al, ; Santana and Miller, ), their jaw muscles vary significantly in terms of scaling relationships, physiological cross‐sectional areas (PCSA), lever arms, and relative contribution to the forces required to open or close the jaw (Herrel et al ; Santana et al ; Santana and Curtis this issue). Noctilionoids that consume hard fruit and vertebrates have short and broad skulls with a high mechanical advantage, and their m. temporalis produces a greater moment about the temporomandibular joint (TMJ) relative to other jaw adductors (Herrel et al, ; Nogueira et al, ; Santana et al, ; Dumont et al, ; Santana and Cheung, ).…”
mentioning
confidence: 99%
“…Larger bats exhibit cranial morphologies that may allow them to consume relatively larger and harder prey (Aguirre et al, 2003;Freeman, 1984;Freeman & Lemen, 2010;Santana & Cheung, 2016;Santana et al, 2010) ( Figure 5). Broader zygomatic arches and a more pronounced sagittal crest can accommodate larger temporalis (jaw closing) muscles that can produce more forceful bites (Christiansen & Adolfssen, 2005;Santana et al, 2010;Senawi, Schmieder, Siemers, & Kingston, 2015). Similarly, a relatively shorter and wider rostrum allows for more forceful bites and a greater resistance to torsional forces when chewing hard prey (Dumont, Piccirillo, & Grosse, 2005;Freeman & Lemen, 2010;Santana et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In the hypothetical situation of geometric similarity, the expected scaling of muscle force with body mass is 0.67 (Biewener, ). Previous studies in bats found larger slopes (1.17–1.31) for phyllostomids (Aguirre et al ., ; Freeman & Lemen, ) and a slope similar to ours in a study across many old world bat families (Senawi et al ., ). We found the hypothetical isometric value of 0.67 to be close (or equal) to the lower limits of the confidence intervals for slopes in both ivBF and estBF.…”
Section: Discussionmentioning
confidence: 99%